2021
DOI: 10.1515/zna-2020-0317
|View full text |Cite
|
Sign up to set email alerts
|

Ternary-hybrid nanofluids: significance of suction and dual-stretching on three-dimensional flow of water conveying nanoparticles with various shapes and densities

Abstract: Increasing knowledge of hybrid nanofluid can be traced to its unique improvement of thermal performance and enhancement of heat transfer rate as applicable in the dynamics of fuel and coolant in automobiles. However, the case of water-based nanofluid conveying three kinds of nanoparticles (i.e., ternary-hybrid nanofluid) with various shapes and densities is far-fetched. The transport phenomena of water conveying smaller densities nanoparticles (i.e., copper nanotubes, graphene, and aluminum oxide) and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Microelectronics, propulsion, heat exchangers, military manufacturing, grinding, solar water heating, acoustics, transportation, and naval structures are all examples of hybrid nanofluid uses. Thanaa Elnaqeeb et al [ 11 ] demonstrated a colloidal mixing of three different nanoparticles in ternary hybrid nanofluids. The viscosity of the five ternary hybrid nanofluid variants increases as the concentration rises.…”
Section: Background Informationmentioning
confidence: 99%
“…Microelectronics, propulsion, heat exchangers, military manufacturing, grinding, solar water heating, acoustics, transportation, and naval structures are all examples of hybrid nanofluid uses. Thanaa Elnaqeeb et al [ 11 ] demonstrated a colloidal mixing of three different nanoparticles in ternary hybrid nanofluids. The viscosity of the five ternary hybrid nanofluid variants increases as the concentration rises.…”
Section: Background Informationmentioning
confidence: 99%
“…Utilizing more than one kind of nanoparticle, and the ratios between the different particles, can affect the nanofluid properties. In a heat transfer application, the use of ternary nanofluids has demonstrated an increase in the Nusselt number of nanofluids [48]. Mousavi et al [49] measured the thermal conductivity of water-based nanofluids with MgO, CuO, and TiO 2 nanoparticles in different ratios to one another.…”
Section: Thermal Conductivity Of Ternary Nanofluidsmentioning
confidence: 99%
“…Animasaun et al [ 7 ] exemplified the three-dimensional ternary nanofluids considering suction effect and bi-stretching surface. Yook et al [ 8 ] investigated the ternary fluid past convectively heated sheet considering the effect of heat sink/source and magnetic flux density.…”
Section: Introductionmentioning
confidence: 99%